Nesfatin-1 suppresses autophagy of chondrocytes in osteoarthritis via remodeling of cytoskeleton and inhibiting RhoA/ROCK signal pathway - Lifeng Jiang; Safwat Adel Abdo Moqbel; Junxiong Zhu; Qiangchang Fu; Jiabin Lai; Changjian Lin; Lidong Wu (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Autophagy and cytoskeleton integrity of chondrocytes are a considered as major factors in the progression of osteoarthritis (OA) involving excessive chondrocyte apoptosis and senescence. Nesfatin-1, an adipokine, has been reported to be closely related to cell autophagy and cytoskeleton malfunction. Our previous study found that nesfatin-1 was highly correlated with OA progress in OA patient, and the expression of nesfatin-1 rises in knee articular tissue, serum and chondrocytes. In current study, we aimed to explore the therapeutic effect of nesfatin-1 on OA and its molecular mechanism related to chondrocyte autophagy and cytoskeleton malfunction. We firstly demonstrated that nesfatin-1 effectively suppressed excessive autophagy of OA chondrocytes at both gene and protein levels. Meanwhile, we also found that nesfatin-1 significantly improved cytoskeleton integrity by showing higher F-actin/G-actin ratio, as well as more organized actin fiber structure. Mechanistically, utility of RhoA activator and inhibitor revealed that regulation of autophagy and cytoskeleton integrity via nesfatin-1 was realized via RhoA/ROCK pathway. We also confirmed that nesfatin-1 significantly ameliorated IL-1β induced cartilage degeneration via destabilization of the medial meniscus (DMM) model. Overall, our study indicates that nesfatin-1 might be a promising therapeutic molecule for OA intervention.